First-trimester 3D fetal neurosonography: five standardised views - Fred Ushakov; Adalina Sacco; Pranav Pandya (Journal of Obstetrics and Gynaecology)
Background There are several international guidelines for foetal anomalies scanning at 11–14 weeks’ gestation. The aim of this study is to present our first-trimester specialist neurosonography protocol with examples of pathology in order to develop a systematic approach to evaluating the first-trimester foetal brain.Methods Women undergoing a first-trimester foetal medicine ultrasound scan between 2010 and 2020 for multiple indications underwent neurosonography according to a set protocol. 3D transvaginal brain examination was performed in all cases (2000 pregnancies scanned). We retrospectively reviewed all imaging to develop this protocol.Results We propose that the following five axial-plane parallel views should be obtained when performing neurosonography in the first trimester, moving from cranial to caudal: 1. Lateral ventricles; 2. Third ventricle; 3. Thalamus and mesencephalon; 4. Cerebellum; 5. Fourth ventricle. Examples of these images and abnormalities that can be seen in each plane are given.Conclusions We have presented a specialist protocol for systematically assessing the foetal brain in the first trimester and given examples of pathology which may be seen in each plane. Further work is needed to prospectively assess detection rates of major abnormalities using this protocol and assess the reproducibility and learning curve of this technique.